PERSPEKTIF PENJATUHAN PIDANA MATI BAGI PELAKU PENGULANGAN TINDAK PIDANA KORUPSI - Ameylinda Monica Widhiyanti, (2021)
Corruption crime as an extra ordinary crime still happening a lot in Indonesia. The punishment that given to corruption perpetrator which tends to be light and does not make a deterrent to cause a repetition of corruption. The repetition of corruption crime could be punish by death penalty as stipulated in the corruption act. But it's implementation still having problems from the pros and cons with death penalty. The author formulates a problem raised in this study regarding death penalty as a way to eradite corruption crime and the problem to imposing death penalty to the guilty one. The purpose of this research is to know and analyze death penalty to eradite corruption crime and to know what's the problem to imposing death penalty to repetition perpetrator of corruption crime. The type of this research is normative juridical research. The government should be fixing the weaknesses of all the acts so the acts will have it's consistency between one and another.